THE EFFECTS OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) ON CORPORATE PERFORMANCE - Martha, Henri; Khomsiyah, Khomsiyah (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2023)
This study has the purpose to discuss the effect of Environmental, Social, Governance (ESG) disclosure on market performance. The variables used in this study involved the dependent variable (Tobin's Q), the independent variable (ESG disclosure score), and the moderating variable (ROA and ROE). The population is obtained by the companies listed on the Indonesia Stock Exchange in 2016-2020. Sampling is done by purposive sampling. According to the purposive sampling method, samples are from 67 companies. The multiple regression analysis is used as the analytical method in this study. The results of this study revealed that Tobin's Q has a negative and significant effects on ESG score through ROA and ROE.